Eficacia de tres extractos botánicos para el control de trips en el cultivo de pimiento (Capsicum annuum L.), en la parroquia San Blas, cantón Urcuquí, provincia de Imbabura - Cruz Peñaherrera, Mayra Maritza (2018)
VII. SUMMARY In the present work, the effectiveness of three extracts in one and in the mix for the control of thrips of the pepper crop in the sector of San Blas canton Urcuqui, province of Imbabura, was evaluated in order to determine the effectiveness of extracts Botanists in the control of the thrips in the pepper, to evaluate the agronomic behavior and its yield in harvested fruit quality and to carry out the economic analysis of each of the treatments applied at 45, 60 and 75 days. After the first application. The variables: population of live individuals before and after treatments, extract efficacy, plant height, stem thickness and number, fruit size and yield were evaluated. The economic analysis was performed according to the yield (kg / ha) and the cost of each treatment. All variables were subjected to the analysis of variance and the Tukey test at 5% was used to determine the statistical difference between the means of the factors and interpretation. The experimental results determined that: averages of plant height, stem thickness, number, fruit size and yield showed significant positive differences, marked by the treatment of Extract of Ruda + Ajo + Quinua (3000cc / has) on the other treatments Of Extracts applied and compared to the control; The Extract of Ruda + Garlic + Quinua, presented the highest percentage of effectiveness reaching with significant results in comparison to the control and the other treatments. In addition, with the Ruda + Ajo + Quinua treatment, economic profits of 80% were obtained where the (Witness) obtained 47%